Rising From The Slump: The Role Of Human Resource Management In Improving The Performance Of Saung Angklung Udjo - Budi Rismayadi; Mumun Maemunah (SEAN Institute, 2024)
Saung Angklung Udjo, as one of the cultural tourism destinations in Bandung, faces major challenges in maintaining its existence, especially related to effective human resource management. This study aims to analyze the role of Human Resource Management in improving the performance of Saung Angklung Udjo after the downturn experienced due to the impact of the Covid-19 pandemic. This study uses a descriptive qualitative approach with data collection through in-depth interviews, observations, and documentation studies. The results of the study show that the Covid-19 Pandemic has had a significant impact on the tourism sector in Indonesia, including Saung Angklung Udjo in Bandung, which experienced a drastic decline in the number of visitors due to social restrictions and the closure of tourist attractions. To recover from this downturn, Saung Angklung Udjo needs to improve its management, especially in the management of human resources. Steps taken include evaluating organizational structures, implementing training programs to improve employee skills and motivation, and creating a healthy work culture. In addition, it is important to build a positive image of the organization through open communication and fair implementation of policies. The human resource development strategy must consider Sundanese cultural values, including arts and culture training, mentorship between senior and young artists, and increasing multicultural awareness. With these steps, Saung Angklung Udjo can strengthen its position as a sustainable arts and culture center.